The inhibitory effect of Thymus vulgaris extracts on the planktonic form and biofilm structures of six human pathogenic bacteria - Zinab Mohsenipour; Mehdi Hassanshahian (Mashhad University of Medical Sciences, 2015)
Objective: Microorganisms are responsible for many problems in industry and medicine because of biofilm formation. Therefore, this study was aimed to examine the effect of Thymus vulgaris (T. vulgaris) extracts on the planktonic form and biofilm structures of six pathogenic bacteria. Materials and methods: Antimicrobial activities of the plant extracts against the planktonic form of the bacteria were determined using the disc diffusion method. MIC and MBC values were evaluated using macrobroth dilution technique. Anti-biofilm effects were assessed by microtiter plate method. Results: According to disc diffusion test (MIC and MBC), the ability of Thymus vulgaris (T. vulgaris ) extracts for inhibition of bacteria in planktonic form was confirmed. In dealing with biofilm structures, the inhibitory effect of the extracts was directly correlated to their concentration. Except for the inhibition of biofilm formation, efficacy of each extract was independent from type of solvent. Conclusion: According to the potential of Thymus vulgaris (T. vulgaris ) extracts to inhibit the test bacteria in planktonic and biofilm form, it can be suggested that Thymus vulgaris(T. vulgaris )extracts can be applied as antimicrobial agents against the pathogenic bacteria particularly in biofilm forms.